2021
DOI: 10.3389/fphys.2021.790182
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Was Involved in the Process of Liver Injury During Intra-Abdominal Hypertension

Abstract: Background: Intestinal damage caused by intra-abdominal hypertension (IAH) and abdominal compartment syndrome (ACS) can lead to the ectopic gut microbiota, which can contribute to liver injury via portal veins. Therefore, it is speculated that gut microbiota disorder caused by IAH/ACS may result in liver injury. The relationship between gut microbiota and IAH/ACS-related liver injury was investigated in this study.Methods: A model of IAH was established in rats, and 16S rRNA sequencing was analyzed for gut mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Escherichia_Shigella can adversely affect liver lipid metabolism [51]. Zhao et al [52] found that increases in the relative abundance levels of Proteobacteria and Escherichia_Shigella in the intestine of rats can cause liver damage. In the present study, compared with levels in the CG, the relative abundance levels of Proteobacteria and Escherichia_Shigella in the MG were increased.…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia_Shigella can adversely affect liver lipid metabolism [51]. Zhao et al [52] found that increases in the relative abundance levels of Proteobacteria and Escherichia_Shigella in the intestine of rats can cause liver damage. In the present study, compared with levels in the CG, the relative abundance levels of Proteobacteria and Escherichia_Shigella in the MG were increased.…”
Section: Discussionmentioning
confidence: 99%
“…Another future approach to reduce the influence of CIT on IAH and ACS could be machine perfusion of donor organs. Regarding the pathomechanism of organ injury due to IAH/ACS, Zhao et al published an interesting animal study [ 41 ] showing that IAH/ACS-induced gut microbiota dysbiosis highly contributes to liver injury. Our study provides vital basics for future investigations into these relevant aspects of the pLT setting.…”
Section: Discussionmentioning
confidence: 99%
“…The primary disease combined with IAH and vasomotor changes quickly induces a pathological gut microflora or dysbiome that has adverse consequences for the host 25 . Animal studies have reported that IAH decreases the abundance and diversity of the gut microbiota and increases the relative amounts of pathogenic lipopolysaccharide-secreting Proteobacteria 26 , 27 . Further, dysbiotic faeces from previously IAH-injured rats exacerbates the injury 27 .…”
Section: The Open Abdomen In Intra-abdominal Sepsismentioning
confidence: 99%
“…Animal studies have reported that IAH decreases the abundance and diversity of the gut microbiota and increases the relative amounts of pathogenic lipopolysaccharide-secreting Proteobacteria 26 , 27 . Further, dysbiotic faeces from previously IAH-injured rats exacerbates the injury 27 .…”
Section: The Open Abdomen In Intra-abdominal Sepsismentioning
confidence: 99%